Penerapan Hukuman Mati Bagi Pelaku â€ŽTindak Pidana Korupsi - muwahid muwahid (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2015)
Abstract: Research on the application of the death penalty â€Žfor perpetrators of corruption is a research library , with the â€Žpurpose to find out: first, setting the death penalty in law of â€Žcorruption; secondly, the application of the death penalty for â€Žperpetrators of corruption in a human rights perspective. â€ŽPrimary data were obtained from the legislation, secondary â€Ždata obtained from the criminal law books, law journals, and â€Žlegal dictionaries. Data was collected to study the document. â€ŽWhile the use of data analysis techniques "content analysis". â€ŽThe results showed; first, setting the death penalty in the Act â€Žeradication of corruption, there is only one article setting that â€Žarticle 2, paragraph (2) In the article explained that the death â€Žpenalty can be applied to the perpetrators of corruption in " â€Žcertain circumstances"; secondly, the application of the death â€Žpenalty for corruptors if only textually examined, then the â€Žapplication of the death penalty is contrary to human rights â€Žas dicantukan in Article 28A paragraph (1), 28I (1), in â€Žconjunction with Article 4 of Law No. 39 of 1999, in â€Žconjunction with Article 3 of the Universal Declaration . â€ŽHowever, if examined contextually by using extentif and â€Žteleological interpretation, the actual application of the death â€Žpenalty does not conflict with Human Rights.â€Ž Abstrak: Penelitian tentang penerapan hukuman mati bagi â€Žpelaku tindak pidana korupsi ini merupakan penelitian â€Žpustaka, dengan tujuan untuk mengetahui: pertama, â€Žpengaturan hukuman mati dalam hukum korupsi; kedua, â€Žpenerapan hukuman mati bagi pelaku tindak pidana korupsi â€Ždalam perspektif hak asasi manusia. Data primer diperoleh â€Ždari undang-undang, data sekunder diperoleh dari buku-buku â€Žhukum pidana, jurnal hukum, dan kamus hukum. Data â€Ždikumpulkan untuk mempelajari dokumen. Sedangkan teknik â€Žanalisis data dengan menggunakan â€œcontent analysisâ€. Hasil â€Žpenelitian menunjukkan; pertama, menetapkan hukuman mati â€Ždalam pemberantasan UU Tindak Pidana Korupsi, hanya â€Žterdapat pada satu pasal saja, yaitu Pasal 2 ayat (2). Dalam â€ŽPasal tersebut dijelaskan menjelaskan bahwa hukuman mati â€Ždapat diterapkan kepada pelaku tindak pidana korupsi dalam â€Žkeadaan tertentu. Kedua, penerapan hukuman mati bagi â€Žkoruptor jika hanya diteliti secara tekstual, maka penerapan â€Žhukuman mati bertentangan dengan hak asasi manusia â€Žsebagaimana dicantukan dalam Pasal 28A ayat (1), 28I (1), jo â€ŽPasal 4 Undang-undang Nomor 39 Tahun 1999, jo Pasal 3 dari â€ŽUDHR. Namun, jika diteliti secara kontekstual dengan â€Žmenggunakan intrepetasi extentif dan interpretasi teleologis, â€Žsebenarnya penerapan hukuman mati tidak bertentangan â€Ždengan Hak Asasi Manusia.â€Ž